Projekt Management textbook - Dulzon A. A. Alfred Andreevich (Tomsk, TPU Press, 2006)
This manual, which corresponds to the academic program of the course "Project Management", sets forth basic information about all the phases of project management from preparation to completion in a concise form. The course is delivered at the International Management Institute of Tomsk Polytechnic University. It is intended for students of Institutions of Higher Education and for all those who are interested in project management.